2008
DOI: 10.1556/abiol.59.2008.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and metabolic responses to extended cold exposure in rats

Abstract: In this work, we investigated whether extended cold exposure increases oxidative damage and susceptibility to oxidants of rat liver, heart, kidney and lung which are metabolically active tissues. Moreover in this study the effect of cold stress on some of the lipid metabolic mediators were studied in rat experimental model. Male albino Sprague-Dawley rats were randomly divided into two groups: The control group (n=12) and the cold-stress group (n=12). Tissue superoxide dismutase (SOD), catalase (CAT), glutathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…It was observed that cold stress exposure increased lipid depletion in adrenal gland and glycogen depletion in hepatocytes, which supports previous studies [5,6]. We noted that this NMDA antagonist, currently used to treat subjects with moderate to severe Alzheimer's disease [4,5], significantly attenuated glycogen and lipid depletion in liver and adrenal gland, respectively, caused by cold stress in health Wistar rats.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It was observed that cold stress exposure increased lipid depletion in adrenal gland and glycogen depletion in hepatocytes, which supports previous studies [5,6]. We noted that this NMDA antagonist, currently used to treat subjects with moderate to severe Alzheimer's disease [4,5], significantly attenuated glycogen and lipid depletion in liver and adrenal gland, respectively, caused by cold stress in health Wistar rats.…”
Section: Discussionsupporting
confidence: 90%
“…Histological slides were reviewed by a pathologist. Previous publications validated this procedure [5,6,19]. …”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Exposure to low temperatures is considered to be an important stressing physical agent 4,5. Previous studies have reported that acute exposure to cold stress can damage heart tissue6 and cause lipid depletion in the adrenal gland and glycogen depletion in the liver,68 thus suggesting that sympathetic activity and oxidative stress are the sources of these injuries.…”
Section: Introductionmentioning
confidence: 99%